2010
DOI: 10.1016/j.envsoft.2009.07.015
|View full text |Cite
|
Sign up to set email alerts
|

An econometric analysis of SARS and Avian Flu on international tourist arrivals to Asia

Abstract: This paper compares the impacts of SARS and human deaths arising from Avian Flu on international tourist arrivals to Asia. The effects of SARS and human deaths from Avian Flu are compared directly according to the number of human deaths. The nature of the short run and long run relationship is examined empirically by estimating a static line fixed effect model and a difference transformation dynamic model, respectively. Empirical results from the static fixed effect and difference transformation dynamic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(48 citation statements)
references
References 20 publications
2
44
0
2
Order By: Relevance
“…Kuo, Chen, Tseng, Ju, and Huang (2008) also used a time series model to investigate the impacts of infectious diseases, including Avian Flu and severe acute respiratory syndrome, on international tourist arrivals in Asia. The empirical results indicated that the numbers of affected cases had a significant impact in the case of SARS (see also Mao, Ding, & Lee, 2010;McAleer, Huang, Kuo, Chen, & Chang, 2010), but for Avian Flu.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Kuo, Chen, Tseng, Ju, and Huang (2008) also used a time series model to investigate the impacts of infectious diseases, including Avian Flu and severe acute respiratory syndrome, on international tourist arrivals in Asia. The empirical results indicated that the numbers of affected cases had a significant impact in the case of SARS (see also Mao, Ding, & Lee, 2010;McAleer, Huang, Kuo, Chen, & Chang, 2010), but for Avian Flu.…”
Section: Literature Reviewmentioning
confidence: 98%
“…For example, the Severe Acute Respiratory Syndrome (SARS) is a serious disease which affected tourism in most Asian countries. Many authors have analyzed the impacts of various disease outbreaks on travel and tourism for various countries using econometric methods (Chen, Jang, & Kim, 2007;Chien & Law, 2003;Kou, Chen, Tseng, Ju, & Huang, 2008;McAleer, Huang, Kuo, Chen, & Chang, 2010;McKercher & Chon, 2004;WTTC, 2003;Wilder-Smith, 2006;Tung & Chao, 2011;Oukil, Channouf, & Al-Zaidi, 2016;Cuhadar, 2014). By contrast, Cankurt and Subasi (2016), Song, Li, Witt, andAthanasopoulos (2011), Turner (2015) and many others used structural TS analysis to model and forecast tourist demand.…”
Section: A Brief Review Of Literaturementioning
confidence: 99%
“…One of the indirect effects of an outbreak is that it has a detrimental economic impact on a country. This is exemplified by the SARS and avian virus outbreaks in 2003, which led to a huge loss of around US$20 million for the tourism industry in most affected Asian countries such China, Hong Kong, Singapore and Vietnam because of an ineffective surveillance system [6]. For this reason, we need to be able to rely on an accurate detection system to monitor for signs of an emerging outbreak.…”
Section: Introductionmentioning
confidence: 99%